Fake Qualifications and the Challenge of regulating Higher Education in Southern Africa - Jimu, Ignasio M. (Modern Africa: Politics, History and Society, 2018)
This article examines the prevalence and implications of fake qualifications and the need for an effective regulatory regime to contain fake higher education qualifications. Fake qualifications by definition refer to false academic and professional credentials, regardless of the source, which means they may be acquired from illegitimate institutions, superficially legitimate institutions or through illegitimate means from legitimate institutions. The qualifications are in this sense illegitimate both in the manner in which they are obtained and also in terms of what they signify. The research for this article shows that the clandestine nature of the production and issuance and its global reach make it difficult to quantify, but also to control the use of fake qualifications and to manage their impact locally, nationally and globally. Drawing from several cases, it is apparent that the phenomenon of fake qualifications defies the integrity and legitimate expectations from an education system and is a serious challenge to education and ethical standards. It is further argued that given the challenges presented by the proliferation of fake qualifications generally, and in southern Africa in particular, it is imperative for higher education institutions, regulatory bodies, employers and the general public to develop a keen interest in the subject of fake qualifications and to cooperate in order to contain the menace.